1994
DOI: 10.1021/np50114a016
|View full text |Cite
|
Sign up to set email alerts
|

Absolute Stereochemistry of Neohalicholactone from the Brown Alga Laminaria sinclairii

Abstract: Phytochemical analysis of an extract from the brown alga Laminaria sinclairii led to the isolation of neohalicholactone, a cyclopropyl-containing oxylipin previously isolated from a marine sponge, Halichondria okadai. Unequivocal stereochemical analysis of the C-15 hydroxyl group showed this isolate to be of opposite overall absolute stereochemistry compared to that proposed for halicholactone, a related compound from the sponge, and by our inference, sponge-derived neohalicholactone. Comparison of chiroptical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
20
0

Year Published

1996
1996
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 1 publication
2
20
0
Order By: Relevance
“…58 Critcher et al reported the synthesis of the right-hand hemisphere 59 and the first asymmetric total synthesis of halicholactone (80) and neohalicholactone (81), 55 confirming the original assignments of absolute configuration of the stereocenters of 81 originally proposed by Yamada and Clardy. 53 They also demonstrated, through the preparation of diastereomers of 81, 55 that the natural product isolated by Proteau et al 54 was, in fact, a C15 epimer of this nine-membered lactone.…”
Section: Halicholactone and Neohalicholactonementioning
confidence: 91%
See 1 more Smart Citation
“…58 Critcher et al reported the synthesis of the right-hand hemisphere 59 and the first asymmetric total synthesis of halicholactone (80) and neohalicholactone (81), 55 confirming the original assignments of absolute configuration of the stereocenters of 81 originally proposed by Yamada and Clardy. 53 They also demonstrated, through the preparation of diastereomers of 81, 55 that the natural product isolated by Proteau et al 54 was, in fact, a C15 epimer of this nine-membered lactone.…”
Section: Halicholactone and Neohalicholactonementioning
confidence: 91%
“…52 In 1991, the relative stereochemistry of all stereocenters of neohalicholactone (81) has been determined by X-ray crystallography as shown below. 53 Some years later, Proteau et al 54 isolated 81 from the brown alga Laminaria sinclairii, and its absolute configuration was suggested to be the opposite to that previously postulated.…”
Section: Halicholactone and Neohalicholactonementioning
confidence: 97%
“…Subsequently, an X-ray study of neohalicholactone (37) provided relative stereochemistry in this series (57). A potential complication in the structure of halicholactone and neohalicholactone was introduced by isolation and structural description of "neohalicholactone" from the Pacific brown alga L. sinclairii (58). From this kelp we had earlier isolated a variety of 15-1ipoxygenase products, all of which had a 15S stereochemistry (e.g., 15S-HETE, 38, see above) (9).…”
Section: Neohalicholactones From a Sponge And A Brown Algamentioning
confidence: 99%
“…[1,2] Many syntheses rely on the same key reaction, the Nozaki-Hiyama-Kishi reaction [3] starting with vinyl iodides 3 (3a [4] /3b [5] ). Thep resent study led to ag eneral approach towards intermediate 4.…”
mentioning
confidence: 99%
“…Z-configured homoallylic alcohols are often found as structural motifs in natural products,f or example in oxylipines such as solandelactone A + B( 1)a nd neohalicholactone (2)a nd related compounds of marine origin (Scheme 1). [1,2] Many syntheses rely on the same key reaction, the Nozaki-Hiyama-Kishi reaction [3] starting with vinyl iodides 3 (3a [4] /3b [5] ). Thep resent study led to ag eneral approach towards intermediate 4.…”
mentioning
confidence: 99%